PREFERENSI TIKUS (Rattus argentiventer) TERHADAP JENIS UMPAN PADA TANAMAN PADI SAWAH - Alfian Rusdy (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2008)
Preference of Rat (Rattus argentiventer) to Kinds of Baits on Rice Crop Alfian Rusdy dan Irvandra Fatmal Jurusan HPT Fakultas Pertanian Unsyiah Kuala Banda Aceh ABSTRACT The purpose of this research was to identify preference of rats to several kinds of foods. This research was conducted at rice field at Aneuk Glee Village, sub district of Indrapuri, district of Aceh Besar. This research used Randomized Block Design non factorial, consisting of 6 treatments. They were unhulled paddy, rice, split rice, corn, split corn and corn powder. The treatment was repeated 4 times. The variables observed were percentage of damage plant, trapped rats, and ratio of male rat to female rat. The result of this research showed that preference of the rat was significantly affected by kinds of food. Among the treatments, unhulled paddy was the most preferred. However, at percentage of damage plant, the rats preferred rice to other baits. The ratio of rats trapped was high at male rats. This proved that male rats in addition to getting the food were looking for their pairs, because female rats stayed more in the pit for feeding activity.